Queen of Dreams - Chitra Divakaruni (Abacus, 2005)
In QUEEN OF DREAMS, Chitra Banerjee Divakaruni once more spins a fresh, spellbinding story of transformation. Rakhi, a young artist and divorced mother living in Berkeley, California, is struggling to keep her footing, with her family and her world in alarming transition. Her mother is a dream-teller, born with the ability to share and interpret the dreams of others, to foresee and guide them through their fates. This gift fascinates Rakhi, but also isolates her from her mother's past in India and the dream world she inhabits, and she longs for something to bring them closer. Caught beneath the burden of her painful secret, Rakhi's solace comes in the discovery, after her mother's death, of her dream journals, which begin to open the long-closed doors to her past. As Rakhi's mother writes 'A dream is a telegram from the hidden world'. In lush elegant prose, Divakaruni has crafted a vivid and enduring dream that reveals hidden truths about the world we live in, from which readers will be reluctant to wake.